Bamboo leaf-chitosan compound green corrosion inhibitor and preparation method thereof
By combining bamboo leaf extract and chitosan solution, bamboo leaf-chitosan compound green corrosion inhibitor was prepared, solving the harm problems of traditional corrosion inhibitors to the environment, achieving efficient metal anti-corrosion and antibacterial effects, and environmentally friendly and pollution-free.
Patent Information
- Application Number
- CN202411660723.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-04-08
AI Technical Summary
The preparation process of traditional corrosion inhibitors is complex, and their use and waste will have an impact on the ecosystem. The existing green corrosion inhibitors still have room for improvement in improving the anti-corrosion and antibacterial ability of metals.
By combining bamboo leaf extract with chitosan solution, combining the sustained release ability of bamboo leaf extract and the antibacterial effect of chitosan, bamboo leaf-chitosan compound green corrosion inhibitor was prepared.
This corrosion inhibitor significantly improves the anti-corrosion and bacteriostatic ability of metals, has long-term effects, is environmentally friendly and pollution-free, and can effectively extend the service life of metal materials.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal corrosion inhibitors, and specifically relates to a bamboo leaf-chitosan composite green corrosion inhibitor and a preparation method thereof. Background Art
[0002] As the most common engineering material, metal is widely used in various engineering practices due to its excellent mechanical properties. However, in harsh working environments, the durability of the material will be seriously challenged, resulting in a significant shortening of its service life. This not only seriously affects production efficiency, but also brings considerable economic losses.
[0003] Corrosion is a process in which metals react with surrounding oxygen, water or other chemicals in a harsh environment, resulting in the formation of corrosion products on the metal surface. Corrosion inhibitors usually act on the metal surface to form a protective film on the metal surface through physical adsorption, chemical reaction or physical and chemical interaction, reducing the contact area between the metal and the corrosive medium and slowing down the corrosion efficiency.
[0004] Although traditional corrosion inhibitors can also play a role in reducing the corrosion rate, their preparation process is complicated and they are usually synthesized from a variety of harmful chemicals. Their use and disposal will have an impact on the ecosystem. In order to reduce the harm of traditional corrosion inhibitors to the human body and the environment, green corrosion inhibitors have gradually become the preferred option in the field of corrosion protection. These advanced corrosion inhibitors are mainly based on natural, renewable raw materials, reducing dependence on non-renewable resources at the source. During the preparation and use process, green corrosion inhibitors are committed to reducing or completely avoiding the use of environmentally harmful chemicals, thereby minimizing the negative impact on the ecosystem while ensuring the metal corrosion protection effect. The research and development of more efficient green corrosion inhibitors can not only effectively extend the service life of metal materials, but also make positive contributions to achieving sustainable development goals and environmental protection. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a bamboo leaf-chitosan composite green corrosion inhibitor.
[0008] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing a bamboo leaf-chitosan composite green corrosion inhibitor, characterized in that: comprising:
[0009] Washing, drying, crushing and sieving the bamboo leaves to obtain bamboo leaf debris;
[0010] The bamboo leaf debris is added into an anhydrous ethanol solution and soaked, and ultrasonic extraction is performed and then soaked again, and the process is repeated three times to obtain a solution; the solution is filtered and then rotary evaporated to obtain a bamboo leaf extract corrosion inhibitor;
[0011] adding chitosan into the citric acid solution and stirring to obtain a chitosan solution;
[0012] The bamboo leaf extract corrosion inhibitor, chitosan solution and water are mixed, stirred and ultrasonically dispersed to obtain the bamboo leaf-chitosan composite green corrosion inhibitor.
[0013] As a preferred embodiment of the preparation method of the present invention, the mass ratio of the bamboo leaf extract corrosion inhibitor to the chitosan solution is 0.5-1.5:2-4.
[0014] As a preferred embodiment of the preparation method of the present invention, the concentration of the anhydrous ethanol solution is 75-95%.
[0015] As a preferred embodiment of the preparation method of the present invention, the concentration of the citric acid solution is 0.1-0.3 mol / L.
[0016] As a preferred embodiment of the preparation method of the present invention, the addition ratio of chitosan to citric acid solution is 5-15g:1L.
[0017] As a preferred embodiment of the preparation method of the present invention, the addition ratio of the bamboo leaf powder to the anhydrous ethanol solution is 5-15g:100ml.
[0018] As a preferred embodiment of the preparation method of the present invention, the soaking time is 5 to 8 hours.
[0019] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a bamboo leaf-chitosan composite green corrosion inhibitor to obtain a bamboo leaf-chitosan composite green corrosion inhibitor.
[0020] As a preferred embodiment of the bamboo leaf-chitosan composite green corrosion inhibitor of the present invention, the corrosion inhibition rate of the bamboo leaf-chitosan composite green corrosion inhibitor is 95.93-97.13%.
[0021] Another object of the present invention is to overcome the deficiencies in the prior art and provide a bamboo leaf-chitosan composite green corrosion inhibitor for use in the field of metal corrosion inhibitors.
[0022] Beneficial effects of the present invention:
[0023] (1) The present invention adopts the method of preparing a composite of bamboo leaf extract and chitosan solution, and by combining the high sustained-release ability of bamboo leaf extract with the corrosion inhibition and bactericidal effect of chitosan, the anticorrosion and antibacterial ability of the green corrosion inhibitor on metals is greatly improved. The green corrosion inhibitor is suitable for various metal materials, has the characteristics of long-term improvement of metal anticorrosion and antibacterial ability, and is environmentally friendly and pollution-free.
[0024] (2) The present invention combines the corrosion inhibition effect of bamboo leaf extract with the antibacterial ability of chitosan, which can improve the anticorrosion and antibacterial ability of metals and can have a long-term effect. In addition, bamboo leaves and chitosan are both environmentally friendly compounds, which are pollution-free to the natural environment and can alleviate the environmental pressure caused by corrosion. DETAILED DESCRIPTION
[0025] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0026] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0027] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0028] Unless otherwise specified, all raw materials used in the examples of the present invention are commercially available, as shown in Table 1 for details.
[0029] Table 1
[0030]
[0031] The experimental chitosan and bamboo leaves were purchased online, and the other experimental drugs were from the laboratory's regular drug list.
[0032] Example 1
[0033] This embodiment provides a method for preparing a bamboo leaf-chitosan composite green corrosion inhibitor:
[0034] (1) Wash the bamboo leaves and dry them at 110°C, crush them and pass them through a 30-mesh sieve for storage.
[0035] (2) Weigh 10 g of the sieved bamboo leaf debris, add it to 100 ml of 80% ethanol solution and soak it for 6 hours, then use ultrasonic extraction for 30 minutes and soak it for another 6 hours, and repeat three times (repeat soaking, extraction, and soaking three times).
[0036] (3) Filter the solution of step (2) to remove the bamboo leaf residue, and rotary evaporate the filtered solution to separate the solvent ethanol to obtain a bamboo leaf extract corrosion inhibitor (BL).
[0037] (4) Weigh 10 g of chitosan and add it to 1 L of 0.2 mol / L citric acid solution, and stir at 500 r / min at 50°C for 1 h to obtain a chitosan solution (CS) after it is completely dissolved.
[0038] (5) 1 ml of the bamboo leaf extract corrosion inhibitor obtained in the above step (3) and 3 ml of the chitosan solution obtained in step (5) were added to the same beaker and diluted to 100 ml with distilled water, followed by stirring at 500 r / min for 3 h, and then using ultrasonic dispersion for 10 min to finally obtain a bamboo leaf-chitosan composite green corrosion inhibitor with a concentration of (1% BL-3% CS).
[0039] Example 2
[0040] The difference from Example 1 is that in step (5), 1 ml of bamboo leaf extract corrosion inhibitor is replaced with 0.5 ml of bamboo leaf extract corrosion inhibitor to obtain (0.5% BL-3% CS) bamboo leaf-chitosan composite green corrosion inhibitor.
[0041] Example 3
[0042] The difference from Example 1 is that in step (5), 1 ml of bamboo leaf extract corrosion inhibitor is replaced with 1.5 ml of bamboo leaf extract corrosion inhibitor to obtain (1.5% BL-3% CS) bamboo leaf-chitosan composite green corrosion inhibitor.
[0043] The bamboo leaf-chitosan composite green corrosion inhibitor prepared in Examples 1 to 3 was tested for corrosion inhibition rate:
[0044] The material prepared in the embodiment of the present invention was tested for sustained release performance as follows:
[0045] The corrosion inhibition performance was evaluated by the weight loss method. A laboratory simulated pipeline circulating water platform was used. Under specific water quality conditions, corrosion inhibitors were added and metal test pieces were hung in the simulated circulating water pipeline for corrosion tests. The corrosion inhibition rate was then calculated based on the weight loss of the metal samples before and after the experiment. The specific conditions for evaluating the slow-release performance are as follows:
[0046] (1) The water quality of the circulating pipeline is prepared by using an aqueous solution prepared by 3-6 wt% NaCl and 0.5-1 wt% bamboo leaf-chitosan composite green corrosion inhibitor as the water quality condition for testing the performance of the corrosion inhibitor.
[0047] (2) Use Q235 steel specimens with a mass of 10 to 20 g as test samples.
[0048] (3) The Q235 steel test piece was hung in the circulation pipe of the above water quality environment for corrosion test, and the experimental time was 5 to 7 days.
[0049] (4) Measure the mass of the Q235 steel specimen before and after the test, and obtain its sustained release rate based on the ratio of the mass after the test to the mass before the test.
[0050] Table 2
[0051]
[0052]
[0053] It can be seen from the above table that the concentration of BL has a significant effect on the corrosion inhibition efficiency of the compound corrosion inhibitor. When the BL concentration is 0.5%, the slow-release efficiency of the slow-release agent decreases. As the BL concentration increases, the slow-release efficiency gradually increases. When the BL concentration is 1%, the slow-release efficiency is the largest. When the BL concentration exceeds 1%, the slow-release efficiency tends to be stable. Bamboo leaf extract contains a variety of chemical components such as amino acids, fatty acids, alkaloids, phenols, polysaccharides, flavonoids, etc. These components contain a large number of functional groups such as hydroxyl, carboxyl, and amine. On the one hand, the N, O and other atoms in these groups have high electronegativity and lone pairs of electrons, which can coordinate with the empty d orbitals of Fe atoms on the surface of the steel sample to form a chemical adsorption film, reducing the interaction between Fe atoms and H + The reactivity of the amine groups and H + Combined to form positive ions, they are adsorbed in the cathode region due to electrostatic effects, hindering H + The best technical effect can be obtained when the BL concentration in the present invention is 1%.
[0054] Example 4
[0055] The difference from Example 1 is that in step (5), 3 ml of chitosan solution is replaced by 2 ml of chitosan solution to obtain (1% BL-2% CS) bamboo leaf-chitosan composite green corrosion inhibitor.
[0056] Example 5
[0057] The difference from Example 1 is that in step (5), 3 ml of chitosan solution is replaced by 4 ml of chitosan solution to obtain (1% BL-4% CS) bamboo leaf-chitosan composite green corrosion inhibitor.
[0058] The bamboo leaf-chitosan composite green corrosion inhibitor prepared in Examples 4 to 5 was tested for corrosion inhibition rate:
[0059] Table 3
[0060] Example 1 Example 4 Example 5 Corrosion inhibition rate (%) 97.13 95.93 96.75
[0061] As can be seen from the table above, the CS concentration has a significant effect on the performance of the corrosion inhibitor. This is because chitosan itself has a corrosion inhibition effect. Too low or too high a concentration will affect the effect of chitosan on metal ions. According to the results in the table above, the best technical effect can be obtained when the CS concentration in the present invention is 3%.
[0062] Comparative Example 1
[0063] (1) Wash the bamboo leaves and dry them at 110°C, crush them and pass them through a 30-mesh sieve for storage.
[0064] (2) Weigh 10 g of the preserved bamboo leaves, add them into 100 ml of 80% anhydrous ethanol solution and soak for 6 hours, then use ultrasonic extraction for 30 minutes and soak for another 6 hours, and repeat three times.
[0065] (3) Filter the solution of step (2) to remove the bamboo leaf residue, and rotary evaporate the filtered solution to separate the solvent ethanol to obtain a bamboo leaf extract corrosion inhibitor (BL).
[0066] (4) 1 ml of the bamboo leaf extract corrosion inhibitor obtained in step (3) above was added to the same beaker and diluted to 100 ml with distilled water, followed by stirring at 500 r / min for 3 h to finally obtain a bamboo leaf corrosion inhibitor with a concentration of (1% BL).
[0067] Comparative Example 2
[0068] (1) Weigh 10 g of chitosan and add it to 1 L of 0.2 mol / L citric acid solution, and stir at 500 r / min at 50°C for 1 h to obtain a chitosan solution (CS) after it is completely dissolved.
[0069] (2) 3 ml of the chitosan solution obtained in the above step was added to the same beaker and diluted to 100 ml with distilled water, followed by stirring at 500 r / min for 3 h to finally obtain a chitosan corrosion inhibitor with a concentration of (3% CS).
[0070] The corrosion inhibition rate of the bamboo leaf-chitosan composite green corrosion inhibitor prepared in Comparative Examples 1 to 2 was tested:
[0071] Table 4
[0072] Example 1 Comparative Example 1 Comparative Example 2 Corrosion inhibition rate (%) 97.13 92.81 58.72
[0073] It can be seen from the above table that compared with conventional single-type corrosion inhibitors, the bamboo leaf-chitosan compound green corrosion inhibitor is not only more environmentally friendly, but also has a more efficient corrosion inhibition level.
[0074] Comparative Example 3
[0075] The difference between this comparative example and Example 1 is that the bamboo leaves are replaced with wolfberries, and the rest of the preparation processes are the same as those in Example 1 to prepare a wolfberry-chitosan green corrosion inhibitor.
[0076] Table 5
[0077] Example 1 Comparative Example 3 Corrosion inhibition rate (%) 97.13 87.13%
[0078] It can be seen from the above table that the wolfberry extract, which also has an antiseptic effect, is prepared into a wolfberry-chitosan green corrosion inhibitor with chitosan according to the same process and also has a certain sustained release rate, but the sustained release effect is lower than the bamboo leaf-chitosan composite green corrosion inhibitor in Example 1.
[0079] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A method for preparing a bamboo leaf-chitosan composite green corrosion inhibitor, characterized in that: include, Washing, drying, crushing and sieving the bamboo leaves to obtain bamboo leaf debris; The bamboo leaf debris is added into an anhydrous ethanol solution and soaked, and ultrasonic extraction is performed and then soaked again, and the process is repeated three times to obtain a solution; the solution is filtered and then rotary evaporated to obtain a bamboo leaf extract corrosion inhibitor; adding chitosan into the citric acid solution and stirring to obtain a chitosan solution; The bamboo leaf extract corrosion inhibitor, chitosan solution and water are mixed, stirred and ultrasonically dispersed to obtain the bamboo leaf-chitosan composite green corrosion inhibitor.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the bamboo leaf extract corrosion inhibitor to the chitosan solution is 0.5-1.5:2-4.
3. The preparation method according to claim 1, characterized in that: The concentration of the anhydrous ethanol solution is 75-95%.
4. The preparation method according to claim 1, characterized in that: The concentration of the citric acid solution is 0.1-0.3 mol / L.
5. The preparation method according to claim 4, characterized in that: The addition ratio of the chitosan to the citric acid solution is 5-15g:1L.
6. The preparation method according to claim 3, characterized in that: The addition ratio of the bamboo leaf powder to the anhydrous ethanol solution is 5-15g:100ml.
7. The preparation method according to claim 3, characterized in that: The soaking time is 5 to 8 hours.
8. The bamboo leaf-chitosan composite green corrosion inhibitor prepared by the preparation method according to claims 1 to 7.
9. The bamboo leaf-chitosan composite green corrosion inhibitor according to claim 8, characterized in that: The corrosion inhibition rate of the bamboo leaf-chitosan composite green corrosion inhibitor is 95.93-97.13%.
10. Use of the bamboo leaf-chitosan composite green corrosion inhibitor as claimed in claim 8 in the field of metal corrosion inhibitors.
Citation Information
Cited By
Multifunctional corrosion inhibitor as well as preparation method and application thereof
CN122466471A